INDIAN TRIBAL RITUALS AND FESTIVALS OF LODHAS OF MAYURBHANJ IN ODISHA: A HISTORICAL ANALYSIS - Ratnakar Mohapatra; Majhi, Hutasan (International Journal of Psychosocial Rehabilitation, 2020)
The Lodhas of Mayurbhanj of Odisha have distinct rituals and festivals, which are very interesting study for the scholars to study the tribal culture of Eastern India. For the writing of this article, both the primary and secondary sources are used to authenticate the conception of the rituals and festivals of Lodha tribe of Mayurbhanj in Odisha. The main Lodha hamlets are found to be set up in the Suliapada and Morada, C.D. Blocks of the Mayurbhanj district of Odisha. The people of Lodha tribe perform different types of traditional rituals and festivals, out of which some are found to be changed due to the impact of neighbouring Hindu culture. It is clearly known from the field survey that there is no temple for the place of their worship. The sacred places of the Lodhas are Mandapa, Thana , Xahira or Jaheera, etc. The important annual ritual-festivals observed by the Lodhas are Sitala puja , Chandi puja, Natun Hanri, Dhana muthi , Baram or Garam Puja, Raja parva , Ashadhi puja-Chitau parva , Jathel , Gahma parva ,Ganesh puja, Nuakhia parva , Dassehara parva, Lakshmi puja , Bandana puja , Karama Puja , Sikara thakurani puja , Makara parva , Magha puja , Phula puja , etc. The present article is proposed to analyze the prevalent rituals and festivals observed by the Lodhas of Mayurbhanj of Odisha in Eastern India. Methodologically, both the primary and secondary sources have been used by the authors for writing of the present article.